Uma análise da modalização em uma videoanimação: estratégias de construção de sentido - Silva, Amanda Jackeline Santos da (2021)
The popularization of technological resources provides greater accessibility to multisemiotic texts, regarding not only consumption, but also the production of these texts. In this perspective, there is a plurality of semiotic resources composing these texts, such as images, colors, sounds, movements, among many others, that cooperate for the production of the senses. It is then emphasized that the texts that are produced cover needs, interests related to the various situations of interaction in the social context, thus emphasizing strategies that were used in order to interact with the interlocutors, that is, the reading and understanding of a text must take into account all the semiotic resources that compose it, since the cooperation between these resources can show the positioning, intentions, feelings and attitudes of its producer, both in static texts and in moving texts. Considering the above and based on the theoretical assumption of Leal and Pinto (2009), who point out that modalizations can appear implicitly in the most different discursive genres, even though they are not instantiated by linguistic markers, the question that guides this research is: How is it presented? the phenomenon of modalization in multisemiotic texts in the context of analysis of the semiotic-discursive organization proposed by GDV? In this sense, this research aims to analyze how the phenomenon of modalization is configured in multisemiotic texts in motion, in a restricted way, in video animation, with a view to expanding the study of the modalities recommended by GDV. The relevance of the research is emphasized in order to contribute to the expansion of studies related to multisemiotic texts in movement, considering that the expansion of visual and sound resources in the social practices of language cooperates to bring the reader closer, as well as to suggest interpretative paths that contemplate the multiple semioses in the production of meanings of texts so widespread in contemporary times. The research is outlined by an analytical theoretical bias aiming to substantiate the basic assumptions that concern the GDV theory (KRESS; VAN LEEUWEN, 2006; SILVA, 2017; BRITO AND PIMENTA, 2009), to the modalization as a discursive phenomenon (BRONCKART, 2012; CASTILHO E CASTILHO, 2002; NEVES, 2007; KOCH, 2011 and 2012) to multisemiotic texts (SILVESTRE; VIEIRA, 2015; SEGATO, 2013; ROJO; MOURA, 2012) and to the genre Videoanimation (FERREIRA; ALMEIDA, 2018; RODRIGUES, 2010; ; DIAS; SILVA; SILVEIRA, 2019), which will subsidize the analysis of the video animation “Allegory of Long Spoons”. As a result, some points deserve to be highlighted: a) studies on multisemiotic texts in motion are scarce in the literature; b) GDV can illuminate the analysis of texts in motion; c) Video animations can favor reflective reading processes, in order to contemplate different languages; d) Colors, lighting and framing can act as non-verbal modalizers in the construction of a given project of saying multisemiotic texts in motion or static; e) the four types of modalizations, instantiated by non-verbal modalizers, are quite recurrent in video animations demarcating the enunciative position of their producers. Thus, it is hoped that this research can contribute significantly to the expansion of this theoretical framework and that in this way it can contribute to linguistic science, bringing new reflections that instigate other possibilities of analysis on video animation genre, so present in our daily lives, as well as other discursive genres in movement that emerge in contemporary times